2019
DOI: 10.1158/1078-0432.ccr-19-1680
|View full text |Cite
|
Sign up to set email alerts
|

A Single-Arm, Multicenter, Phase II Study of Camrelizumab in Relapsed or Refractory Classical Hodgkin Lymphoma

Abstract: Purpose: For classical Hodgkin lymphoma (cHL), programmed death-l (PD-1) is a well-recognized attractive target. This multicenter, single-arm, phase II study evaluated the efficacy and safety of camrelizumab, a humanized highaffinity IgG4 mAb against PD-1, in Chinese patients with relapsed or refractory cHL.Patients and Methods: Patients who had failed to achieve a remission or experienced progression after autologous stem cell transplantation or had received at least two lines of systemic chemotherapies were … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
96
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 125 publications
(111 citation statements)
references
References 20 publications
3
96
2
Order By: Relevance
“…1). Twenty-seven of them were excluded as they were conference abstracts, leaving 13 eligible studies consisting of 1063 patients for analysis [20][21][22][23][24][25][26][27][28][29][30][31][32] . Basic information of these studies were shown in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…1). Twenty-seven of them were excluded as they were conference abstracts, leaving 13 eligible studies consisting of 1063 patients for analysis [20][21][22][23][24][25][26][27][28][29][30][31][32] . Basic information of these studies were shown in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…They have demonstrated similar anti-cancer activities as those developed in the USA although some of them demonstrated higher in vitro binding affinity to the PD-1. Three of them have been approved for treating classical Hodgkin's lymphoma whereas one has been approved for treating melanoma [34][35][36][37][38][39][40]. None of them have been approved for more common types of malignancies such as NSCLC.…”
Section: Simple Addition: the Traditional Methods Of Combination Ici Dmentioning
confidence: 99%
“…For example, for patients with relapsed or refractory classical Hodgkin lymphoma, tislelizumab (anti-PD-1) achieved an objective response rate of 87.1% and a complete response of 62.9%, in a phase II, single-arm, multicenter study [7]. Similarly, the complete response rate of camrelizumab (anti-PD-1) was 28.0%, with a partial remission rate of 48.0% [29].…”
Section: Resistance To Pd-1/pd-l1 Blockade Therapymentioning
confidence: 99%